Rheumatic Exercise for Menopausal Women in the Perumnas II Pontianak Health Center Area - Diena Juliana; Masmuri Masmuri; Lintang Sari; Fauzan Saputra; Meli Piatun Khatifah (Jurnal Pengabdian Masyarakat, 2023)
Purpose: Menopause is a phase experienced by women due to the declining function of the ovaries, resulting in the cessation of the menstrual cycle. Various complaints arise in women entering menopause, especially joint and muscle pain, as well as psychological complaints. This condition can affect the quality of life of menopausal women. Therefore, it is necessary to educate women on how to reduce these complaints. This educational activity aims to increase women's knowledge about menopause and the appropriate self-management of menopausal complaints. Method: This activity is conducted in the community served by the Perumnas II Pontianak Health Center. Participants are members of the Pre-Elderly Prolanis Kejora Manis group. The activity methods include explanations, observational techniques, demonstrations, and practical exercises. Practical Applications: The outreach activity is divided into two sessions. The first session focuses on educating about menopausal symptoms and how to address them, followed by the second session, which involves demonstrations and joint exercises for rheumatism. Conclusion: Rheumatism exercises should be taught to pre-menopausal women for daily practice to improve comfort and adaptation to the menopausal condition.